Factorization and criticality in the anisotropic XY chain via correlations - Cakmak, Baris [UNESP]; Karpat, Goektug [UNESP]; Fanchini, Felipe F. [UNESP] (Mdpi Ag, 2015)
In this review, we discuss the zero and finite temperature behavior of various bipartite quantum and total correlation measures, the skew information-based quantum coherence and the local quantum uncertainty in the thermal ground state of the one-dimensional anisotropic XY model in a transverse magnetic field. We compare the ability of the considered measures to correctly detect or estimate the quantum critical point and the non-trivial factorization point possessed by the spin chain.
Keywords: XY spin chain; Quantum phase transitions; Quantum correlations; Total correlations; Quantum coherence; Wigner–Yanase skew information